Methods for low bitrate coding enhancement part I: Spectral restoration - Gampp, Patrick; Uhle, Christian; Disch, Sascha; Hellmuth, Oliver; Prokein, Peter; Havenstein, Julia; Karampourniotis, Antonios; Herre, Jürgen (Proceedings of the AES International Conference, 2017)
Perceptual audio coders are widely used when storage space or streaming bandwidth for audio content is limited. If the used bitrate is low, various coding artifacts can be introduced that degrade the perceived audio quality. A suite of algorithms has been developed to conceal these coding artifacts and to improve the perceived sound quality in automotive environments. This paper is a continuation of a previous paper and introduces two post-processing algorithms for restoring the spatial signal quality of decoded compressed audio signals. Both algorithms work single-ended, i.e. without access to the bitrate or other side information. The merit of the algorithms is demonstrated by listening tests. A second part of the paper describes algorithms that enhance the spatial image.
CRIS-Team Scopus Importer:2023-02-20